2022
DOI: 10.3390/jcm11185425
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Findings and Endothelial Perturbation in a COVID-19 Low-Intensity Care Unit

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…When combined with coagulation parameters and compressive ultrasound (CUS), the Soldati protocol proved to be useful in evaluating the length of hospitalization and the need for O2 therapy [39]. Notably, the Soldati score demonstrated being a good predictor of fatality (AUC 0.878, sensitivity 87.5%, specificity 81.7%), and helpful in discerning whether patients would benefit from HFNC or MV [40].…”
Section: Lung Ultrasound Scores For Predicting Severity Treatment Res...mentioning
confidence: 99%
See 2 more Smart Citations
“…When combined with coagulation parameters and compressive ultrasound (CUS), the Soldati protocol proved to be useful in evaluating the length of hospitalization and the need for O2 therapy [39]. Notably, the Soldati score demonstrated being a good predictor of fatality (AUC 0.878, sensitivity 87.5%, specificity 81.7%), and helpful in discerning whether patients would benefit from HFNC or MV [40].…”
Section: Lung Ultrasound Scores For Predicting Severity Treatment Res...mentioning
confidence: 99%
“…Several of these scores have been correlated with other laboratory or clinical parameters to increase their utility in clinical settings [39,48]. Notably, Boero et al developed the "COVID-19 Worsening Score" (COWS) [49].…”
Section: Lung Ultrasound Scores For Predicting Severity Treatment Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…Only four trials reported t-PA levels in surviving and dead COVID-19 patients [25,33,34]. The t-PA values were respectively: 15.33 ± 8.01 for patients who survived to hospital discharge, and 19.04 ± 11.88 for patients who died in hospital due to COVID-19 (SMD = −0.50; 95% CI: −2.45 to 1.44; p = 0.61; Fig.…”
Section: Meta-analysismentioning
confidence: 99%